The Cochrane database of systematic reviews
Abstract: (Producer) A full text database containing systematic reviews of mainly randomized controlled trials. The reviews are highly structured, evidence is included or excluded on the basis of explicit quality criteria to minimize bias. When appropriate, meta-analysis is used to combine the findings of individual studies to provide an overall estimate of effectiveness. The reviews in CDSR are regularly updated as new information becomes available and in response to comments and criticisms.